2005
DOI: 10.1128/cdli.12.6.700-704.2005
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Whole-Blood Gamma Interferon Release for Clinical Assessment of Cellular Immunity in Patients with Active Coccidioidomycosis

Abstract: Assessment of the cellular immune response in coccidioidomycosis has epidemiologic and prognostic importance. Measurement of delayed-type hypersensitivity to skin testing has been used in the past to determine cellular immunity in coccidioidomycosis. However, no skin tests are currently available in the United States. Assay of gamma interferon (IFN-␥) release in whole blood in response to incubation with antigen has been used to assess cellular immunity in tuberculosis. We used a similar assay using the coccid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Peripheral blood cells from patients with DCM produce less IFN-g in response to Coccidioides antigen than cells from those with milder disease. 58,59 Treatment of mice with IFN-g was able to protect mice from systemic infection. 60 A few human patients with extrapulmonary disease have been treated successfully with IFN-g as well (as discussed later), supporting the importance of this cytokine in fighting CM.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Peripheral blood cells from patients with DCM produce less IFN-g in response to Coccidioides antigen than cells from those with milder disease. 58,59 Treatment of mice with IFN-g was able to protect mice from systemic infection. 60 A few human patients with extrapulmonary disease have been treated successfully with IFN-g as well (as discussed later), supporting the importance of this cytokine in fighting CM.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Based on previous observations (12,13), it was surprising that Th1 cytokines in subjects with nonmeningeal disseminated coccidioidomycosis were similar to those in subjects with pulmonary disease and healthy immune donors. To explore this further, we examined cytokine concentrations based on the time from diagnosis to the time of assay.…”
Section: Overview Of Subjectsmentioning
confidence: 99%
“…Moreover, this cellular immune response appears to be long-lived and protective (15). In vitro studies have suggested that control of infection is associated with the release of T-helper type 1 (Th1) cytokines, such as interleukin-2 (IL-2) and gamma interferon (IFN-␥), from peripheral blood mononuclear cells (PBMC) (1)(2)(3)(4)(5)13).…”
mentioning
confidence: 99%
“…Finally, we attempted to ascertain the memory phenotype of antigen-stimulated lymphocytes from naturally immune donors. In all of this work, we used the antigen preparation T27K, since it has consistently been shown to induce specific Th1 responses from coccidioidal antigen immune individuals (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation